The effects of mindfulness-based stress management programme among nurses in Hospital Universiti Sains Malaysia - Wei, Ooi Heong (2020)
Introduction: Nurses have a more incredible opportunity to have stress among healthcare workers. Stressful condition at the workplace has a high risk for burnout and psychological distress. Brief mindfulness intervention has a role in decreasing stress. Objective: This study aimed to explore the effectiveness of the one-day mindfulness intervention for stress reduction on hospital nurses. Methods: This was a quasi-experimental, single group, pre-post intervention study design. Nurses from different speciality areas (n = 35) in Hospital Universiti Sains Malaysia were recruited through convenience sampling. The intervention included a one-day (eight hours) brief mindfulness workshop and monthly one-hour group practice session for three months. A set of validated Malay self-administered questionnaire was used to measure perceived stress, anxiety, depression, and mindfulness at a base line of one week before the mindfulness intervention and after completion of the study at three months. The questionnaire encompassed Depression, Anxiety, and Stress Scale (DAAS), Perceived Stress Scale 10 (PSS 10), and Mindful Attention Awareness Scales (MAAS). Results: There were statistically significant reductions in scores of stress perception (p = 0.04, 95% CI 0.06-2.92) and anxiety (p = 0.04, 95% CI 0.06-2.34) at post-intervention. The level of mindfulness reported no significant increase from pre- to post-intervention (p = 0.71, 95% CI -3.09-4.52). This study also found mindfulness as a factor in reducing stress perception (p < 0.001) at post-intervention. Conclusion: Brief mindfulness intervention is effective in reducing stress and anxiety among nurses.